Comparison of endoparasite infestation in semi commercial and scavenging village chicken - Razali, Nurul Suhada (2016)
The level of endoparasitic infestation in semi commercial village chicken and scavenging village chicken in a village located in Simpang Renggam Kluang, Johor were compared. 6 random chicken feces samples were obtained from semi commercial village chicken from Aqil Aqilah farm and 6 random chicken feces samples were obtained from the surrounding area within the village. From the laboratory test done to detect the quantity of the parasite, it revealed that there was absence of helminths ova in all samples obtained. However, coccidial oocysts were detected in some of the samples. There is 1 sample from the semi commercial chicken with count of 0 oocysts per gram,3 samples from the semi commercial chicken with count of 50 oocysts per gram, 1 sample from the semi commercial chicken with count of 150 oocysts per gram and another 1 sample from the semi commercial chicken with count of 1000 oocysts per gram. For scavenging village chicken, the result revealed there are 4 samples with count of 0 oocysts per gram, 1 sample with 150 oocysts per gram and another 1 with count of 250 oocysts per gram. From the result obtained, there was no significant difference in the coccidial level in semi commercial village chicken and scavenging village chicken based on chi-square test (P>0.05).